Adsorption of arsenite by core–shell K-OMS-2@UiO-66 microspheres: performance and mechanism. (14th August 2020) - Yu, Wenyi; Liang, Qianwei; Yin, Yuwei; Geng, Junjie; Chen, Wei; Tan, Xuanyi; Luo, Hanjin
Abstract : Arsenite (As(iii )) is more toxic and more difficult to remove from water than arsenate (As(v )). Abstract : Arsenite (As(iii )) is more toxic and more difficult to remove from water than arsenate (As(v )). A new nano core–shell-structured K-OMS-2@UiO-66 (K-OMS-2, formula KMn8 O16 · n H2 O) was fabricated via a facile one-step oxidation–coprecipitation method for enhanced As(iii ) removal. Results showed that the maximal adsorption capacity of As(iii ) achieved was 180.10 mg g −1 . The as-synthesized K-OMS-2@UiO-66 adsorbent functions excellently across a broad pH range of 1.5 to 10.0, and the residual concentrations of As(iii ) can drop under 10.0 μg L −1 . Based on XPS and FTIR measurements, it is proposed that the removal mechanism was mainly controlled through a synergistic interaction of surface complexation and hydrogen bonding. As(iii ) was sorbed onto the surface of the sorbent by Zr–O bonds and Mn–O bonds. Mn(iv ) and Mn(iii ) in K-OMS-2@UiO-66 effectively oxidized As(iii ) to As(v ). Then, some negatively charged As(v ) were adsorbed at the positive sites of the adsorbent through electrostatic attraction, while others formed bidentate complexes with the Zr–O bonds. This study develops an attractive sorbent for As(iii ) removal from contaminated water and has a facile and low-cost synthesis process, good As(iii ) sorption performance, and reusability.